Exact Solutions of a Discrete Velocity Model of a Gas With Molecules Dissociation - Monaco, R.; Płatkowski, T. (Engineering Transactions, 1991)
We propose an elementary discrete velocity model of a gas, describing dissociation of diatomic molecules. We found exact analytical solutions to the following problems: 1) wave propagation in an unbounded domain; 2) boundary value problem with boundary conditions admitting sources on the walls.